2020
DOI: 10.3390/v12010067
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Human Mobility on Regional and Global Efforts to Control HIV Transmission

Abstract: HIV prevention and control methods are implemented on different scales to reduce the spread of the virus amongst populations. However, despite such efforts, HIV continues to persist in populations with a global incidence rate of 1.8 million in 2017 alone. The introduction of new infections into susceptible regional populations promotes the spread of HIV, indicating a crucial need to study the impact of migration and mobility on regional and global efforts to prevent HIV transmission. Here we reviewed studies t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 52 publications
(69 reference statements)
2
9
0
Order By: Relevance
“…The mobility indicators depicted strong correlations with epidemiological characteristics for both the lockdown and unlock phases. This trend is consistent with many theoretical studies that have predicted the role of mobility for infectious diseases [ 10 , 52 , 53 ]. Previous studies have demonstrated the utility of mobility in the spread of COVID-19 data globally [ 31 , 54 ].…”
Section: Discussionsupporting
confidence: 92%
“…The mobility indicators depicted strong correlations with epidemiological characteristics for both the lockdown and unlock phases. This trend is consistent with many theoretical studies that have predicted the role of mobility for infectious diseases [ 10 , 52 , 53 ]. Previous studies have demonstrated the utility of mobility in the spread of COVID-19 data globally [ 31 , 54 ].…”
Section: Discussionsupporting
confidence: 92%
“…The mobility indicators depicted strong correlations with epidemiological characteristics for both the lockdown and unlock phases. This trend is consistent with many theoretical studies that have predicted the role of mobility for infectious diseases [10,52,53]. Previous studies have demonstrated the utility of mobility in the spread of COVID-19 data globally [31,54].…”
Section: Discussionsupporting
confidence: 90%
“…The massive local, regional, and international movement of people in a global world also presents a new challenge for humanity -the rapid and encompassing development of epidemics (Bajardi et al, 2011;Eshraghian et al, 2020). In just two months, SARS-CoV-2 spread across the world from the locus of origin in Wuhan (China) infecting approximately 5 million humans by May 20, 2020 (WHO.int).…”
Section: Introductionmentioning
confidence: 99%